Optimization of Kerosene-like Fuels Produced via Catalytic Pyrolysis of Packaging Plastic Waste via Central Composite Design and Response Surface Methodology: Performance of Iron-Doped Dolomite and Activated Carbon - Oratepin Arjharnwong; Tharapong Vitidsant; Aminta Permpoonwiwat; Naphat Phowan; Witchakorn Charusiri (Molecules)
Rapid economic growth has led to an increase in the use of multilayer plastic packaging, which involves complex polymer compositions and hinders recycling. This study investigated the catalytic pyrolysis of plastic packaging waste in a 3000 cm3 semibatch reactor, aiming to optimize kerosene-like hydrocarbon production. The temperature (420–500 °C), N2 flow rate (25–125 mL/min), and catalyst loading (5–20 wt.%) were examined individually and in combination with activated carbon and an Fe-doped dolomite (Fe/DM) catalyst. Central composite design (CCD) and response surface methodology (RSM) were used to identify the optimal conditions and synergistic effects. Pyrolysis product analysis involved simulation distillation gas chromatography (Sim-DGC), gas chromatography/mass spectrometry (GC/MS), and Fourier transform infrared (FT-IR) spectroscopy. The optimal conditions (440 °C, 50 mL/min N2 flow, catalyst loading of 10 wt.% using a 5 wt.% Fe-doped dolomite-activated carbon 0.6:0.4 mass/molar ratio) yielded the highest pyrolysis oil (79.6 ± 0.35 wt.%) and kerosene-like fraction (22.3 ± 0.22 wt.%). The positive synergistic effect of Fe/DM and activated carbon (0.6:0.4) enhanced the catalytic activity, promoting long-chain polymer degradation into mid-range hydrocarbons, with secondary cracking yielding smaller hydrocarbons. The pore structure and acid sites of the catalyst improved the conversion of intermediate hydrocarbons into aliphatic compounds (C5–C15), increasing kerosene-like hydrocarbon production.